2022
DOI: 10.1038/s41467-022-31797-0
|View full text |Cite
|
Sign up to set email alerts
|

Microglia coordinate cellular interactions during spinal cord repair in mice

Abstract: Traumatic spinal cord injury (SCI) triggers a neuro-inflammatory response dominated by tissue-resident microglia and monocyte derived macrophages (MDMs). Since activated microglia and MDMs are morphologically identical and express similar phenotypic markers in vivo, identifying injury responses specifically coordinated by microglia has historically been challenging. Here, we pharmacologically depleted microglia and use anatomical, histopathological, tract tracing, bulk and single cell RNA sequencing to reveal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 93 publications
2
54
1
Order By: Relevance
“…Notably, we uncovered several potential microglial-B cell interactions that will be worthwhile to investigate further. A recent paper by Brennan et al [7] also identified the Ccl3/Ccl4-Ccr5 pair through receptor-ligand analysis that we found to be potentially involved in microglial-B cell recruitment, although in the context of interactions between microglia (Ccl3) and macrophages (Ccr5). B cells also express Ccr5, which means they could respond to this chemokine signal to be recruited into the tissue.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Notably, we uncovered several potential microglial-B cell interactions that will be worthwhile to investigate further. A recent paper by Brennan et al [7] also identified the Ccl3/Ccl4-Ccr5 pair through receptor-ligand analysis that we found to be potentially involved in microglial-B cell recruitment, although in the context of interactions between microglia (Ccl3) and macrophages (Ccr5). B cells also express Ccr5, which means they could respond to this chemokine signal to be recruited into the tissue.…”
Section: Discussionsupporting
confidence: 52%
“…In the Milich study, they specifically excluded lymphocytes from their analysis. B cells have also been found in the other SCI studies in which the cellular changes have been explored by scRNA-seq [4,7]. Our unique data set enabled us to investigate the potential interactions between these two cell types.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Their beneficial effects on axon growth are consistent with the observations of exacerbated functional deficits following disruption of astrogliosis in rodent models ( Faulkner et al, 2004 ; Okada et al, 2006 ; Herrmann et al, 2008 ). Recent gene expression data, by bulk or single-cell RNA sequencing, of reactive astrocytes collected at the lesion from acute to chronic phases of spinal cord injury will aid unbiased discovery of astrocyte-derived factors that can facilitate axon regeneration in the mature mammalian CNS ( Anderson et al, 2016 ; Milich et al, 2021 ; Wahane et al, 2021 ; Wei et al, 2021 ; Brennan et al, 2022 ; Burda et al, 2022 ; Li et al, 2022 ). Given the long-recognized diversity of astrocytes, based on origin, location, injury type, and molecular signatures ( Zhang and Barres, 2010 ; Khakh and Sofroniew, 2015 ), a future challenge will be to define context-dependent astrocyte functions, including their regulation of axon plasticity.…”
Section: Implications For Future Researchmentioning
confidence: 99%